2021
DOI: 10.2478/jee-2021-0043
|View full text |Cite
|
Sign up to set email alerts
|

A novel compact stair-shaped multiband fractal antenna for wireless communication systems

Abstract: The growing demand for enhanced capacities, broadband services, and high transmission speeds to accommodate speech, image, multimedia, and data communication simultaneously puts a requirement for antenna to operate in multiple frequency bands. A novel compact fractal antenna based on self-similar stair-shaped fractal geometry is proposed in this paper. The fractal antenna is designed by modifying the patch antenna through the iterative process using stair-shaped fractal geometry. The third iteration results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…In addition, the transmitted signals were defined as ideal signals from ideal elements. In real-time, the signal transmission scenario is complex [47][48][49] which results in mutual coupling, frequency increment errors, and non-negligible side lobes, etc. Therefore, the comparison between FDA and phased array will be more complex, and may affect the overall efficiency.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…In addition, the transmitted signals were defined as ideal signals from ideal elements. In real-time, the signal transmission scenario is complex [47][48][49] which results in mutual coupling, frequency increment errors, and non-negligible side lobes, etc. Therefore, the comparison between FDA and phased array will be more complex, and may affect the overall efficiency.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Therefore, we can conclude that the performance of the proposed FDA radar has been improved evidently by utilizing non-uniform inter-element spacing and random frequency offsets. Moreover, the proposed non-uniform distribution of array element achieves miniaturization of the antenna [27][28][29] which is an attractive feature for various next-generation applications. The length of the 33elements antenna array with proposed non-uniform dis-…”
Section: 3 Transmit Beampattern Synthesismentioning
confidence: 99%
“…Vipul Sharma et al [20] presented a multiband circular fractal antenna with parasitic SRR, which operates at 3, 5, 6.8, 7.5, and 8.5 GHz. Jaffri et al [21] introduced a stair-shaped fractal antenna that resonated at 3.65, 4.825, and 6.325 GHz. Choukiker et al [22] reported a dual wideband modified Sierpinski square fractal antenna.…”
Section: Introductionmentioning
confidence: 99%